Passive and active two-dimensional photonic crystal components - Märki, Iwan (My University, 2006)
Photonic crystals are periodic dielectric structures having periodicity of the order of the wavelength. Consequently, they offer the ability to control the propagation of electromagnetic waves in a similar way as the periodic potential aspects the electron motion in a semiconductor crystal. By choosing the parameters of the photonic crystal, desired dispersion characteristics such as band gaps for light can be implemented, providing the possibility of creating miniaturized photonic components for integrated optical circuits. In this thesis, two-dimensional photonic crystal components with passive and active functionalities are designed, realized and investigated. The passive components, including photonic crystal cavities, waveguides and tight waveguide bends, are studied by means of far-field and near-field (heterodyne SNOM) measurement techniques addressing loss, quality factors and transmission efficiencies. The ability to tune or modulate the optical properties of photonic crystal devices increases their functionality and opens up new possibilities for applications. We present two ways of perturbing the optical environment near a photonic crystal cavity, enabling tuning and modulation of the in-plane transmission. Optical switching and wavelength tuning is obtained by means of induced thermal and plasma dispersion effects when focusing a laser onto a photonic crystal cavity structure, demonstrating the feasibility of high-speed optical integrated circuits based on silicon structures. On the other hand, tuning of the resonant wavelength and on-off switching of the transmission signal is achieved by probing the optical field confined within the resonant cavity by means of an atomic force microscope (AFM) tip, suggesting an integrated on-off switch or tunable filter. This thesis combines design, fabrication and measurement, thus bringing a better understanding of the fundamental properties of these types of photonic crystals, and helping to pave the way to practical integrated optical circuits.
Thèse de doctorat : Université de Neuchâtel, 2006 ; 1932